2021
DOI: 10.1532/hsf.3837
|View full text |Cite
|
Sign up to set email alerts
|

A New Current to The Armamentarium: Is the CHA2DS2-Vasc-HS Score Predictive of Low Left Internal Mammary Artery (LIMA) Flow in Patients Underwent Coronary Bypass Surgery?

Abstract: Introduction: Left internal mammary artery (LIMA) grafts should be used in patients undergoing CABG. No other procedure results in patency equivalent to that of the left anterior descending coronary artery (LAD)–LIMA bypass graft. The CHA2DS2-Vasc-HS scoring system can be used to successfully predict CAD severity in stable CAD patients. We aimed to investigate the relationship between LIMA flow and the CHA2DS2-Vasc-HS score. Methods: A total of 684 patients, who underwent CABG surgery, were included in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“… 20 Several previous studies have suggested that the CHA2DS2-VASc score can predict the prognosis of patients with various cardiovascular diseases (eg, hypertension, heart failure) regardless of the combination of atrial fibrillation 16 , 21 as well as the low left internal mammary artery (LIMA) flow in patients underwent coronary bypass surgery. 22 And it also can be an independent predictor of in-hospital and long-term prognosis in patients with acute myocardial infarction. 23 In patients with acute coronary syndromes, the CHA2DS2-VASc score is also associated with the occurrence of adverse cardiovascular events and associated with the thrombus burden in patients with acute myocardial infarction undergoing SVG-PCI.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Several previous studies have suggested that the CHA2DS2-VASc score can predict the prognosis of patients with various cardiovascular diseases (eg, hypertension, heart failure) regardless of the combination of atrial fibrillation 16 , 21 as well as the low left internal mammary artery (LIMA) flow in patients underwent coronary bypass surgery. 22 And it also can be an independent predictor of in-hospital and long-term prognosis in patients with acute myocardial infarction. 23 In patients with acute coronary syndromes, the CHA2DS2-VASc score is also associated with the occurrence of adverse cardiovascular events and associated with the thrombus burden in patients with acute myocardial infarction undergoing SVG-PCI.…”
Section: Discussionmentioning
confidence: 99%